Evaluation of the Clinical Efficiency of an Antisickling Polyherbal Formula Drepanoalpha in a Sickle cell disease Patient in Gbado-Lite City (Democratic Republic of the Congo) by Quantum Magnetic Resonance Analyzer - Benjamin Gbolo Zoawe; Koto-te-Nyiwa Ngbolua; Pius T. Mpiana; Ndanga Bikibo Appolinaire; Pangodi Aundagba Jean-Marie; Masengo Ashande Colette; Mudogo Virima (Britain International for Academic Research (BIAR) Publisher, 2019)
Sickle cell disease is a genetic disease linked to the presence of hemoglobin S in the blood and is a major public health problem in Africa. The drugs available are expensive in view of the purchasing power of the majority of the population. The aim of this study was to assess the clinical efficacy of an improved traditional medicine called Drepanoalpha (an anti-sickle cell polyherbal formula) in a homozygous sickle patient using the quantum magnetic resonance analyzer. The results show the relevance of the use of this unconventional technical approach in the sickle cell disease patient treatment evaluation. Indeed, this study showed that Drepanoalpha is effective in vivo and restored homeostatic balance by optimizing some vital functions in the treated patient. The quantum magnetic resonance analyzer is therefore an important away which allows understanding the disorders of the body due to sickle cell disease and their correction post-treatment. It is desirable that the use of this device be validated in the evaluation of the effectiveness of anti-sickling drugs in large-scale clinical trials in rural areas like Nord-Ubangi province. Indeed, this instrument is not only fast, practical, economical, accessible, non-invasive but also easy to use and suitable for this category of research in underprivileged areas. The results obtained are in perfect agreement with the facts observed (recovery of some vital parameters and disappearance of seizures in the patient).